Advances in surface plasmon resonance for analyzing active components in traditional Chinese medicine - Jing Xie; Xian-Deng Li; Mi Li; Hong-Yan Zhu; Yan Cao; Jian Zhang; A-Jing Xu (Elsevier, 2024)
The surface plasmon resonance (SPR) biosensor technology is a novel optical analysis method for studying intermolecular interactions. Owing to in-depth research on traditional Chinese medicine (TCM) in recent years, comprehensive and specific identification of components and target interactions has become key yet difficult tasks. SPR has gradually been used to analyze the active components of TCM owing to its high sensitivity, strong exclusivity, large flux, and real-time monitoring capabilities. This review sought to briefly introduce the active components of TCM and the principle of SPR, and provide historical and new insights into the application of SPR in the analysis of the active components of TCM.